Cambridge primary English learner's book 3 - Lindsay, Sarah (United kingdom : Cambridge university press, 2021)
Cambridge Primary English Learner's Book 3 (Second Edition) is designed for young learners in the third year of primary education, further developing their English language skills. This book builds on the foundation established in earlier levels, with a focus on refining reading, writing, speaking, and listening abilities.
Keywords: English : Textbook